2019
DOI: 10.1155/2019/9739258
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Derived Exosomes Prevent Aging-Induced Cardiac Dysfunction through a Novel Exosome/lncRNA MALAT1/NF-κB/TNF-α Signaling Pathway

Abstract: Aging is a risk factor for cardiovascular disease, and there is no effective therapeutic approach to alleviate this condition. NF-κB and TNF-α have been implicated in the activation of the aging process, but the signaling molecules responsible for the inactivation of NF-κB and TNF-α remain unknown. Exosomes have been reported to improve heart functions by releasing miRNA. Recent studies suggest that lncRNAs are more tissue-specific and developmental stage-specific compared to miRNA. However, the role of lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 39 publications
3
79
0
Order By: Relevance
“…As expected, the AR-lncRNAs, compared with aging-non-regulated lncRNAs (ANR-lncRNAs), showed a stronger correlation with aging course ( Figure S2A ), and were more dynamically expressed during aging in all 11 examined organs ( Figures S2B and S2C ). A few previously reported AR-lncRNAs such as H19 ( Hofmann et al, 2019 ), Malat1 ( Zhu et al, 2019 ), and Neat1 ( White et al, 2015 ) were identified in our AR-lncRNA list, attesting to the validity of our data analysis ( Table S2 ). Notably, the two WAT depots (eWAT and iWAT) had the highest number of AR-lncRNAs among all examined organs ( Figure 2A ; Table S2 ).…”
Section: Resultssupporting
confidence: 73%
“…As expected, the AR-lncRNAs, compared with aging-non-regulated lncRNAs (ANR-lncRNAs), showed a stronger correlation with aging course ( Figure S2A ), and were more dynamically expressed during aging in all 11 examined organs ( Figures S2B and S2C ). A few previously reported AR-lncRNAs such as H19 ( Hofmann et al, 2019 ), Malat1 ( Zhu et al, 2019 ), and Neat1 ( White et al, 2015 ) were identified in our AR-lncRNA list, attesting to the validity of our data analysis ( Table S2 ). Notably, the two WAT depots (eWAT and iWAT) had the highest number of AR-lncRNAs among all examined organs ( Figure 2A ; Table S2 ).…”
Section: Resultssupporting
confidence: 73%
“…16 In addition, human umbilical cord mesenchymal stem cell secreted the exosomes containing MALAT1, which prevent aging-induced cardiac dysfunction via inhibition of NF-κB/TNF-α signaling pathway. 86 Similarly, MALAT1 induced by HBO in HCAECs and HCAECs-derived exosomes could promote angiogenesis via inhibition of miR-92, then up-regulation of KLF2. 57 6 | CONCLUSIONS CVD is the first leading cause of death.…”
Section: Malat1 and Therapymentioning
confidence: 99%
“…found that exosomes released from human umbilical cord MSCs contain MALAT1, which was shown to inhibit the NF-κB/TNF-α pathway in cardiac inflammation. 51 In a similar vein, Sun et al…”
Section: Cardiovascular Systemmentioning
confidence: 85%